Sequential formation and resolution of multiple rosettes drive embryo remodelling after implantation. Issue 11 (November 2018) - Christodoulou, Neophytos; Kyprianou, Christos; Weberling, Antonia; Wang, Ran; Cui, Guizhong; Peng, Guangdun; Jing, Naihe; Zernicka-Goetz, Magdalena
Abstract The morphogenetic remodelling of embryo architecture after implantation culminates in pro-amniotic cavity formation. Despite its key importance, how this transformation occurs remains unknown. Here, we apply high-resolution imaging of embryos developing in vivo and in vitro, spatial RNA sequencing and 3D trophoblast stem cell models to determine the sequence and mechanisms of these remodelling events. We show that cavitation of the embryonic tissue is followed by folding of extra-embryonic tissue to mediate the formation of a second extra-embryonic cavity. Concomitantly, at the boundary between embryonic and extra-embryonic tissues, a hybrid 3D rosette forms. Resolution of this rosette enables the embryonic cavity to invade the extra-embryonic tissue. Subsequently, β1 -integrin signalling mediates the formation of multiple extra-embryonic 3D rosettes. Podocalyxin exocytosis leads to their polarized resolution, permitting the extension of embryonic and extra-embryonic cavities and their fusion into a unified pro-amniotic cavity. These morphogenetic transformations of embryogenesis reveal a previously unappreciated mechanism for lumen expansion and fusion. Using time-lapse microscopy and transcriptome analysis of the post-implantation mouse embryo, Christodoulou et al. show that cavity fusion occurs through the formation and polarized resolution of multiple, multicellular three-dimensional rosettes.